Provincial Fiduciary Obligations to First Nations: The Nexus between Governmental Power and Responsibility - Rotman, Leonard I. (Osgoode Hall Law Journal, 1994)
The Canadian Crown's fiduciary duty to First Nations is entrenched in Canadian Aboriginal rights jurisprudence. More than ten years after the Supreme Court of Canada's decision in Guerin, however, yet to be ascertained are the various emanations of the Crown bound by that duty. This paper argues that both federal and provincial Crowns are properly bound by fiduciary obligations to First Nations. It also suggests that the basis of this assertion may be found in existing jurisprudence, the Canadian Constitution, the spirit and intent of Indian treaties, and in Aboriginal understandings of "the Crown."